Spaces of the mind : narrative and community in the American West - Jahner, Elaine, 1942- (Frontiers of narrative., 2004)
"Spaces of the Mind" reveals how both immigrant European and modern Native communities and individuals use oral and written narratives to define and center themselves in time and space. Elaine A. Jahner skillfully weaves together years of fieldwork among the Standing Rock Sioux in North Dakota, her own memories of growing up in a German-Russian town across the Missouri River from the Standing Rock Sioux, and an illuminating set of narrative concepts. "Spaces of the Mind" proposes a theory of cognitive style that emphasizes the ways in which distinct cultural identities are expressed through the structure of a narrative and the unfolding of its performance, telling, or reading. Themes of creativity and survival amid loss pervade the stories told by Natives about themselves and their past when discussing the inundation of the original Standing Rock Sioux village during the Oahe Dam construction in the 1950s. Immigrant Germans and Alsatians struggled to reconcile the hardships of the northern Plains with what they left behind in the Old World, and the narratives of a German-Russian community reflect and encourage survival in the face of transition. Jahner also studies how two prominent novelists - James Welch, a member of the Blackfeet community, and Mildred Walker, who left her native New England for the West - perceive a single landscape, the state of Montana, and how it has influenced their thought and narratives. "Spaces of the Mind" provides a fresh understanding of Western literature and culture, encourages a reconsideration of the formation and modern character of the American West, and contributes to a fuller appreciation of the significance of narrative. Elaine A. Jahner (1942-2003) was a professor of English at Dartmouth College. She is the co-editor of "Lakota Myth" and "Lakota Belief and Ritual", by James R. Walker, both available in Bison Books editions